Interactions between corporate governance, tourism growth, and corporate performance: the case of listed tourism companies in Türkiye - Katircioglu, Setareh; Ilban Oguzhan, Mehmet; Sezer, Sevgi; Liceli Tahsin, Mehmet (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: This study evaluates interactions between corporate governance, tourism growth, and corporate performance concerning listed tourism companies. Methodology: Panel econometric procedures, including regressions by least squares, fixed effects, random effects and causality analyses were followed using quarterly data ranging from 2013:Q1 to 2023:Q4. Results: The results show that company-level corporate governance proxies and country-level tourism growth exert statistically significant effects on companies financial performance, with mixed directions of corporate governance’s impact. The panel causality test results exhibit two different unidirectional causalities that run (1) from company-level board size to company-level return on assets, and (2) from country-level tourism growth to company-level return on equity. Implications and recommendations: The results reveal that tourism companies need to be encouraged to increase the number of tourists and the number of nights spent in order to achieve better corporate performance. As further research, determinants of leadership styles and their effects on financial performance would provide important clues about the management methods that should be implemented to improve competitiveness and performance. Originality/value: Türkiye was selected as the sample, being one of the top tourist destinations, therefore the results of this study could be generalised for other major tourist destinations, especially those in the Mediterranean region. As far as research questions, econometric methodology, and data type are concerned, this study is the first of its kind to the best of the author’s knowledge.
Argumenta Oeconomica, 2025, Nr 2 (55), s. 151-160
Keywords: tourism; corporate governance; corporate performance; panel data; Turkey